2010
DOI: 10.1590/s1679-45082010ao1546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of semen parameters in semen donors in a ten-year period in the city of São Paulo

Abstract: Evaluation of semen parameters in semen donors in a ten-year period in the city of São Paulo showed that the sperm concentration (R 2 = 19.1%, R 2 = 20.2%, p < 0.0001 respectively) and the oval morphology (R 2 = 13%; R 2 = 13.5%; p < 0.0001, respectively) decreased significantly, even when the first or the second sperm collection is considered. The ejaculated volume showed slight increase during the period for both samples (R 2 = 2.2%, p = 0.048; R-sq = 2.4%. p = 0.038, respectively). All characteristics did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A previous Brazilian study retrospectively investigated the quality of donated semen samples and a decline in both sperm count and normal sperm morphology was observed ( 8 ). To our knowledge, such an investigation has never been conducted in Brazilian sub fertile couples attending an assisted fertilization center for conventional semen analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous Brazilian study retrospectively investigated the quality of donated semen samples and a decline in both sperm count and normal sperm morphology was observed ( 8 ). To our knowledge, such an investigation has never been conducted in Brazilian sub fertile couples attending an assisted fertilization center for conventional semen analysis.…”
Section: Introductionmentioning
confidence: 99%
“…From 1973 to 2011, authors reported a 50-60% decline in male sperm concentration in North America, Europe, Australia, and New Zealand 6 . In Brazil, some authors have also published data on declining concentrations and percentage of morphologically normal sperm 7,8 . Possible reasons for these changes in seminal parameters may be related to lifestyle, habits, age, alcohol or tobacco consumption, as well as endocrine factors, obesity, diet, and coffee consumption 9 .…”
mentioning
confidence: 99%
“…To date, only a single study has evaluated sperm concentration, motility and morphology over a prolonged period in a group of South American (Latin American) men. In this study, conducted between 1992 and 2003 in the city of São Paulo on 182 Brazilian semen donors, a significant reduction in sperm concentration and normal morphology was found (Glina et al, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…However, the results are contradictory and many critics negate this hypothesis as some studies have shown no decrease in semen quality in recent years (Benshushan, Shoshani, Paltiel, Schenker, & Lewin, 1997;Marimuthu, Kapilashrami, Misro, & Singh, 2003). In this study, conducted between 1992 and 2003 in the city of São Paulo on 182 Brazilian semen donors, a significant reduction in sperm concentration and normal morphology was found (Glina et al, 2010). Very little information is available on longitudinal studies on the semen quality in Latin American countries.…”
Section: Introductionmentioning
confidence: 81%